216k views
2 votes
How Would You Solve (2x+1)(x-5)

User Yasseros
by
5.3k points

2 Answers

6 votes

Answer:

The answers are x = -.5 and x = 5

Explanation:

Typically when asked to solve quadratics like this, we are looking for when the equation equals 0. In order to find when the equation is equal to 0, we need to find when each parenthesis is equal to 0.

2x + 1 = 0

2x = -1

x = -.5

x - 5 = 0

x = 5

User Jackotonye
by
5.4k points
4 votes

Answer:

2x^2 - 9x - 5

Explanation:

This is a multiplication problem; it's not an equation and thus can't be "solved." Rather: "Multiply out (2x+1)(x-5)."

(2x+1)(x-5) = 2x^2 - 10x + x - 5, or 2x^2 - 9x - 5. This is the "product" of (2x+1)(x-5).


User GillyD
by
5.9k points